Anatomy of digestive tract of the chicken - Bassler, Charles Earle (My University, 1907)
Introduction: In writing on this subject, the purpose has been to give a few notes that will enable anyone to post mortem a chicken and have some idea of what the normal anatomy should present. The subject is narrowed as title indicates, because chickens are probably the most important division of live stock left largely unstudied and of all systems of organs, those connected with digestion are surely of the greatest economic importance. During the year of 1905, there were 1,500,000,000 dozens of eggs produced in the United States alone, and the present outlook is even brighter than the past record. As the country becomes more populous, the cost of raising other domestic animals will increase, hence a rise in price of meats. For the above reasons and others, the chicken industry is sure to become more important. As it grows so also will the demand for men with a knowledge of their diseases. The intelligent reader of poultry diseases or the veterinarian cannot hope to most thoroughly comprehend these diseases without some conception of the correct conditions and relations of the parts affected. As most poultrymen know, one-half of the chickens dying before marketing are less than a month old and their death at this age is usually from digestive disturbances, therefore to the person who depends upon a brooder for chicks, this subject will possess a peculiar interest. Further I believe the more thorough knowledge of their diseases will stimulate the raising of chickens from a utility standpoint rather than for fancy points, substituting size and quality of bird with increased egg production for fine marks and color of plumage.
Citation: Bassler, Charles Earle. Anatomy of digestive tract of the chicken. Senior thesis, Kansas State Agricultural College, 1907.
Morse Department of Special Collections
Keywords: Chickens; Digestive Tract; Chicken Anatomy; Diseases in Chickens; Theses